Prevalence of Self-Medication among Urban Population Participating Community Pharmacies (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: Self-medication is defined as the individuals who used to treat self-recognized symptoms or illnessesusing and selecting traditional, herbal medicine products. Self-medication permits the consumer or patient to takean active role. However, it is not a completely safe health character, particularly in the irresponsible or unreliablepractice cases. Incorrect self-diagnosis, adverse reactions, masking of severe disease, incorrect dosage, and incorrectchoice of therapy, drug interactions, dependence, and abuse are the potential risks of self-medication. Objective: Theobjective of the study was to determine the prevalence of self-medication in urban population and to identify anyfactors contributing to self-medication in relation to assess the attitude, perception, and knowledge of consumerstoward self-medication. Materials and Methods: Our study was a cross-sectional survey which was conductedover 12 weeks from the month February to May in Jeddah city, K.S.A. Self-administered, validated questionnairewas used to collect the data and questionnaire was designed by reviewing the available research literature. It wasdesigned in the English and Arabic language. Results: A total of 1036 peoples participated in the survey. Mostresponders were female (59.26%) and the males were 40.73%, the participants were predominantly in the age groupof 25–40 years which were 38.41%. About 94.11% of participants are answered in Arabic and 5.88% were answeredin English language. The most common medications consumed without prescriptions were painkillers (93.05%). Thereasons for self-medications were health problems which were not serious (67.18%). Conclusion: In the study ofrational drug use, assessment of self-medication is most important element. The observation of this research shouldform the basis for future interventional plans to increase benefits and decrease risks. In Saudi Arabia, communitypharmacies have the potential to make a great impact in ensuring medicines which are properly utilized.